Digital signal processing: principles, algorithms, and applications - Proakis, John G.; Manolakis, Dimitris G. (New Delhi : Prentice Hall of India, 2007)
Engineering
Keywords: Digital signal; Signal processing; Signals and systems; Analog-to-digital; Frequency analysis; Sampling and reconstruction; Multirate digital signal processing; Linear prediction; Power spectrum